HIV self-management perceptions and experiences of students at one university in South Africa - Siseko Tyabazeka; Wendy Phiri; Regis R. Marie Modeste (AOSIS, 2024)
Background: The public health concern posed by HIV in South Africa is significant, particularly among young adults aged 15-34 years. Within this age range, university students present a unique demographic, concurrently managing their HIV condition and academic pursuits, thus raising concerns about HIV management within university environments. Research into the experiences of South African university students living with HIV is relatively sparse. Objectives: The study aimed to explore the HIV self-management perceptions and experiences of South African university students. Method: The study employed a qualitative research approach grounded in the constructivist paradigm. Data were collected through semi-structured interviews with eight (8) students living with HIV at a university in the Western Cape area in 2021. Data were analysed through thematic analysis. All ethical principles were adhered to, and trustworthiness was ensured. Results: Findings revealed that students utilised various strategies to manage their HIV condition, inclusive of maintaining a positive mindset, and adopting a healthy diet. They encountered obstacles such as experiencing HIV-related stigma, which frequently resulted in elevated stress levels. The potential role of peer support groups was also underscored, with students expressing a desire to participate in such groups to maintain their mental health. Conclusion: Living with HIV is a challenging experience for university students, but self-management of the condition makes life easier for them. Contribution: These findings contribute to the understanding of HIV self-management perceptions and experiences of university students, and can inform the development of a comprehensive supportive structure that addresses their needs.